Perfectionism as a Predictor of General Psychological Distress - Amirah Aminanty Agussalim; Nur Akmal; Novi Yanti Pratiwi (Universitas Negeri Makassar, 2025)
Late adolescence is marked by increased academic demands, intensified social evaluation, and identity transitions that can trigger general emotional distress or General Psychological Distress (GPD). Perfectionism—particularly maladaptive dimensions such as socially prescribed perfectionism (SPP) and evaluative concerns—has been identified as an important risk factor for GPD in high school students. This study aims to examine the effect of perfectionism on GPD in high-achieving high school students in South Sulawesi, with GPD measured using the DASS-42. This study also aims to provide an empirical basis for school-based prevention and intervention strategies. A quantitative survey was conducted on 168 high school/MA students from four schools in South Sulawesi using convenience sampling. Perfectionism was measured using the Indonesian Multidimensional Perfectionism Scale and GPD using the DASS-42. The analysis used simple linear regression with a significance level of 5%. The results of the analysis showed a significant regression model, F(1, 166) = 9.89, p = 0.002, with a coefficient of determination R² = 0.056. Perfectionism had a positive and significant effect on GPD (B = 0.43, SE = 0.14, β = 0.24, t = 3.15, p = 0.002). Although the variance contribution was small, the effect was consistent with the literature that perfectionistic concerns are associated with increased symptoms of depression, anxiety, and stress in adolescents. Perfectionism is a significant predictor of GPD in top tier high school students, underscoring the urgency of interventions targeting maladaptive components through self-compassion training, cognitive restructuring, and/or enhancing psychological flexibility in schools.